Condições de saúde bucal de idosos hospitalizados - Freitas, Daniela Napoleão (2013)
The number of people aged over 60 years, defined as elderly by the Elderly Statute, has grown increasingly in Brazil. Hence, population aging is one of the biggest challenges of contemporary public health, both by the need to promote health, and prevent disease and injury in this population, as well as the growing number of elderly in need of hospital care. Objectives: Describe oral conditions related to dental caries, visible plaque, tartar, tooth loss and the use and need for dental prostheses in elderly patients admitted to the University Hospital of Santa Maria. Methods: It is a cross-sectional descriptive exploratory study, in which queries were performed to the patient record and oral examinations. Results: Was observed the precariousness of oral hygiene of the elderly and that most evident treatment needs involves more complex dental procedures in its execution, represented by the needs extensive restorations and extractions. Conclusions: The results of the study indicate that the oral health status of elderly hospitalized patients is poor, highlighting the need for construction and development of measures to promote recovery and health status of the elderly, and particularly in hospital settings. The presence of oral health teams in hospitals is critical to qualify the health care of elderly hospitalized patients.